(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
El aumento de la violencia y muertes por armas de fuego en Venezuela durante las últimas décadas es otra cara del conflicto social y político que resulta una realidad ilegible para los sectores medios y desde el nivel de análisis exclusivamente psicológico. Para superar estos obstáculos etnocéntricos y epistemológicos, que dificultan comprender los impactos de la violencia estructural, se ha ensayado un dispositivo pedagógico socio-reflexivo en la formación en psicología social en la UCV. A partir del análisis cualitativo de 23 entrevistas y cuestionarios a estudiantes, se sistematizan sus principios organizadores: la reconstrucción narrativa, autoetnográfica e interseccional de la trayectoria social del estudiantado; el diálogo interdisciplinar e interdiscursivo; el cuestionamiento práctico de la relación pedagógica tradicional y la reconsideración de la función pública de los/las intelectuales. Se reportan impactos en los posicionamientos identitarios, las visiones de mundo de los/las participantes y el reconocimiento de la heterogeneidad de mundos de vida. Este ensayo pedagógico puede servir como punto de apoyatura para repensar el qué y el cómo de los procesos formativos de las universidades venezolanas y su papel público en el reconocimiento y diálogo con sujetos sociales y políticos, para transformar, con ellos, las violencias y desigualdades que experimentan. The rise of violence and deaths by fire arms during the past decades in Venezuela is another aspect of the social and political conflict which results in an nonunderstandable reality for middle class sectors, and from an exclusive psychological analysis. In order to overcomen ethnocentric and epistemological obstacles that make structural violence hard to understand, we have undertaken a pedagogical socio-reflexive approach in the study of social psychology at UCV. Based on the qualitative analysis of 23 students interviews and questionnaires, these findings are systematized into the following organizing themes: narrative, autoethnographic and interseccional reconstruction of the social trayectory of students; interdisciplinary and interdiscursive dialogue; the questioning in practice of traditional pedagogical relationships and the reconsideration of the public role of intellectuals. Changes are reported in their identity positionings, participants world views and in the recognition of heterogenous ways of living. This pedagogical essay can serve as starting point for rethinking the what and how of formative processes in Venezuelan universities and their public role in recognizing and entering into dialogue with social and political subjects, in order to transform with them the violences and inequities they experience.